Creating, characterizing, and validating the next generation of mouse models for late‐onset Alzheimer's disease. (December 2021) - Carter, Gregory W; Howell, Gareth R; Lamb, Bruce T.; Oblak, Adrian L; Rizzo, Stacey J Sukoff; Sasner, Michael; Territo, Paul R
Abstract: Background: While mouse models based on early‐onset Alzheimer's disease genetics have proven invaluable in many studies, they have to date had limited success as preclinical models. However, the rapid proliferation of human genetic association studies has identified dozens of high‐confidence genetic loci for late‐onset Alzheimer's disease that can now serve as the basis for new genetically engineered mouse models. Such models promise to increase preclinical translatability. Method: In the MODEL‐AD consortium, we are aggregating human genetic data and creating novel mouse models to more accurately reflect human disease through risk variant knock‐in and targeted deletion. These models are being systematically analyzed with multi‐omic, behavioral, in vivo imaging, and neuropathology measures that are aligned with analogous human data to determine each model's specific disease relevance. Result: We have created 49 new mouse models with genetic risk variants introduced in genes including Apoe, Trem2, Abca7, and others. Direct comparison of mutant effects to changes in human LOAD using transcriptomics, proteomics, metabolomics, and in vivo imaging have revealed distinct, disease‐relevant pathways and processes affected in each model. We have furthermore tested candidate therapeutics in mouse models and identified pathways with alleviated and exacerbated disease‐relevant effects. Finally, all MODEL‐AD models, data, and protocols have been broadly disseminated for unrestricted public use. Conclusion: The creation of novel polygenic models that capture the complexity of late‐onset Alzheimer's disease is an outstanding goal that will be significantly aided by the molecular insights revealed through the creation and characterization of these new models.